Investigations of the directional properties of acoustic field in finite cuboidal spaces (geometrical field analysis) - TAJCHERT, Maria (Archives of Acoustics, 1978)
The paper presents an analysis of the properties of the acoustic field in a cuboidal space with the aid of the geometrical method using computer techniques. The assumptions and a brief description of the method together with the results of calculations for a space of fixed dimensions are presented. The studied properties of the acoustic field are in disagreement with results obtained by the statistical method. The directional properties of field, expressed in terms of energy, have been described as a directional characteristic of the equivalent source. Examples of plotted characteristic curves are given and the effect of various parameters on their form is discussed.